Troponin Aptamer on an Atomically Flat Au Nanoplate Platform for Detection of Cardiac Troponin I - Hyoban Lee; Hyungjun Youn; Ahreum Hwang; Hyunsoo Lee; Jeong Young Park; Weon Kim; Youngdong Yoo; Changill Ban; Taejoon Kang; Bongsoo Kim (Nanomaterials, 2020)
Well-ordered bioreceptors on atomically flat Au surfaces can be a high-performance biosensor. Cardiac troponin I proteins (cTnIs) have been regarded as a specific biomarker for acute myocardial infarction (AMI). Here, we report the accurate detection of cTnIs using an aptamer-immobilized Au nanoplate platform. The single-crystalline and atomically flat Au nanoplate was characterized by atomic force microscopy. For the precise detection of cTnI, we immobilized an aptamer that can strongly bind to cTnI onto an atomically flat Au nanoplate. Using the aptamer-immobilized Au nanoplate, cTnIs were successfully detected at a concentration of 100 aM (2.4 fg/mL) in buffer solution. Furthermore, cTnIs in serum could be identified at a concentration of 100 fM (2.4 pg/mL). The total assay time was ~7 h. Importantly, the aptamer-immobilized Au nanoplate enabled us to diagnose AMI patients accurately, suggesting the potential of the present method in the diagnosis of AMI.